Size‐Distribution Control of Exfoliated Nanosheets Assisted by Machine Learning: Small‐Data‐Driven Materials Science Using Sparse Modeling. Issue 10 (6th September 2021) - Haraguchi, Yuri; Igarashi, Yasuhiko; Imai, Hiroaki; Oaki, Yuya
Abstract: 2D materials exhibit emergent properties originating from their characteristic nanostructures. In general, monolayered and few‐layered nanosheets are obtained by exfoliation of the precursor layered materials. However, lateral‐size distribution of the nanosheets is not easily controlled through the exfoliation because of the unpredictable down‐sizing processes. The present work shows selective syntheses of transition‐metal‐oxide nanosheets with the monodisperse and polydisperse lateral sizes by the assistance of machine learning on small experimental data. The precursor layered composites of host transition‐metal oxides and interlayer organic guests are exfoliated into the surface‐modified nanosheets in organic dispersion media. A prediction model of the size distribution is constructed by sparse modeling, a method of machine learning, on the experimental data. The host‐guest‐medium combinations achieving the monodisperse and polydisperse lateral sizes are recommended by the prediction model. Therefore, the nanosheets with the controlled lateral‐size distribution are selectively obtained in a limited number of the experiments. Moreover, self‐assembly of the polydispersed nanosheets forms the homogeneous thin film exhibiting interference color. The prediction model and its construction method can be applied to the other 2D materials. Moreover, the present work implies that sparse modeling is an effective approach for small‐data‐driven materials science. Abstract : Exfoliation is a general route to obtain 2D materials. However, the down‐sizing processes are not predicted before the experiments and controlled on the basis of experiences. Machine learning is applied to construct the prediction model of the size distribution. AI guides selective syntheses of the monodispersed and polydispersed transition‐metal‐oxide nanosheets in a limited number of the exfoliation experiments.